Side of Onset in Parkinson’s Disease and Alterations in Religiosity: Novel Behavioral Phenotypes - Paul M. Butler; Patrick McNamara; Raymon Durso (Behavioural Neurology)
Behavioral neurologists have long been interested in changes in religiosity following circumscribed brain lesions. Advances in neuroimaging and cognitive experimental techniques have been added to these classical lesion-correlational approaches in attempt to understand changes in religiosity due to brain damage. In this paper we assess processing dynamics of religious cognition in patients with Parkinson’s disease (PD). We administered a four-condition story-based priming procedure, and then covertly probed for changes in religious belief. Story-based priming emphasized mortality salience, religious ritual, and beauty in nature (Aesthetic). In neurologically intact controls, religious belief-scores significantly increased following the Aesthetic prime condition. When comparing effects of right (RO) versus left onset (LO) in PD patients, a double-dissociation in religious belief-scores emerged based on prime condition. RO patients exhibited a significant increase in belief following the Aesthetic prime condition and LO patients significantly increased belief in the religious ritual prime condition. Results covaried with executive function measures. This suggests lateral cerebral specialization for ritual-based (left frontal) versus aesthetic-based (right frontal) religious cognition. Patient-centered individualized treatment plans should take religiosity into consideration as a complex disease-associated phenomenon connected to other clinical variables and health outcomes.